Hot temperatures can force delayed mosquito outbreaks via sequential changes in Aedes aegypti demographic parameters in autocorrelated environments - Chaves, Luis Fernando (2014)
Aedes aegypti L. (Diptera: Culicidae) is a common pantropical urban mosquito, vector of dengue, Yellow Fever and chikungunya viruses. Studies have shown Ae. aegypti abundance to be associated with envi ronmental fluctuations, revealing patterns such as the occurrence of delayed mosquito outbreaks, i.e., sudden extraordinary increases in mosquito abundance following transient extreme high temperatures. Here, we use a two-stage (larvae and adults) matrix model to propose a mechanism for environmental signal canalization into demographic parameters of Ae. aegypti that could explain delayed high temper ature induced mosquito outbreaks. We performed model simulations using parameters estimated from a weekly time series from Thailand, assuming either independent or autocorrelated environments. For autocorrelated environments, we found that long delays in the association between the onset of “hot” environments and mosquito outbreaks (10 weeks, as observed in Thailand) can be generated when “hot” environments sequentially trigger a larval survival decrease and over-compensatory fecundity increase, which lasts for the whole “hot” period, in conjunction with a larval survival increase followed by a fecun dity decrease when the environment returns to “normal”. This result was not observed for independent environments. Finally, we discuss our results implications for prospective entomological research and vector management under changing environments.